AN OVERVIEW OF PREPARATION AND PROPERTIES OF NANOFLUID AS CUTTING FLUID USING VEGETABLE OIL FOR SUSTAINABLE MACHINING PROCESS - Habiby, M. Nuril Anwar (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
Machining processes such as turning, milling, drilling and grinding are currently required to be environmentally friendly, including cutting fluids whose function is to reduce friction, wear and corrosion. Mineral oil is a cutting fluid that is widely used in the manufacturing industry, but the problem is that it is nondegradable and the raw material has the potential to run out. Therefore, this review article aims to discuss a literature review regarding the solution to this problem, namely the use of nanofluids as cutting fluids made from vegetable oil because not much has been discussed in Indonesia. Vegetable oils are more environmentally friendly, the ingredients are abundant in nature, and have excellent lubrication properties. The characteristics of nanofluids as cutting fluids such as thermophysical, rheological and tribological properties are also explored in this review article to find out the latest research. According to the literature, it is found that the use of nano-cutting fluid made from vegetable oil can improve thermal properties and tribological performance to reduce friction and wear in the machining process due to superior cooling and lubrication to produce green manufacturing in the future.